Vocabulary differences in children with and without language delay - Ayuso Lanchares, Alba; Santiago Pardo, Rosa Belén; Ruiz Requies, Inés (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Vocabulary in children with Language Development Disorder (LDD) or with Language Delay (LD) is poorer than in children with typical language development, so we want to know what differences exist between them. 66 infants between 3 and 5 years old have participated; It has been assessed what vocabulary they know, it has been determined that they have less vocabulary (52%) than their homonyms (69%), with the exception of the transport category, in which they have the same results. Finally, the list of categories that children with RL or TDL need to work on is determined.